2011
DOI: 10.1088/1478-3975/8/6/063001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of population density and chemical environment on the behavior ofEscherichia coliin shallow temperature gradients

Abstract: In shallow temperature gradients, changes in temperature that bacteria experience occur over long time scales. Therefore, slow processes such as adaptation, metabolism, chemical secretion and even gene expression become important. Since these are cellular processes, the cell density is an important parameter that affects the bacteria's response. We find that there are four density regimes with distinct behaviors. At low cell density, bacteria do not cause changes in their chemical environment; however, their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…When the sensing channel (i.e. the bacterial signaling machinery which translates temperature stimuli into tumbling bias) does not work (e.g., due to deletion of the receptors), the temperature-dependent swimming speed can still cause the directed cell migration [36]. This is consistent with earlier work [20], [21] and our model where mutant strains lacking all receptors can be described by which leads to as described by Eq.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…When the sensing channel (i.e. the bacterial signaling machinery which translates temperature stimuli into tumbling bias) does not work (e.g., due to deletion of the receptors), the temperature-dependent swimming speed can still cause the directed cell migration [36]. This is consistent with earlier work [20], [21] and our model where mutant strains lacking all receptors can be described by which leads to as described by Eq.…”
Section: Resultssupporting
confidence: 90%
“…Our theory can help explain some recent experiments measuring cellular behaviors in shallow temperature gradients [36], [37]. It was observed that even the mutant bacteria lacking all chemoreceptors are still able to migrate toward high temperature [36], showing that there is an additional channel (other than sensing) in regulating bacterial thermotaxis.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Microorganisms occupy a diverse range of environmental niches, so that characteristic time scales of environmental change range over many orders of magnitude [12][14]. Temporal correlations in environmental structure emerge through day and night cycles, seasons, weather patterns, timescales of host dynamics, and complex physical processes like fluid flow, turbulence, and diffusion [15][18].…”
Section: Introductionmentioning
confidence: 99%
“…The graph of temperature (°C) versus concentration (c/c o ) is shown in Figure 1. The study shows that as the temperature increase from 16 to 44°C, the concentration of Ecoli increase from 0 to 2.5 c/c o [12]. In order to determine the rate of survival of E. coli bacteria in water, an antenna with certain specifications was designed to detect and analyzed survival of E. coli in fresh water, and drinking water.…”
Section: Introductionmentioning
confidence: 99%